Analysis Of The Implementation Of Inclusive Education In Realizing Equitable Access To Education For Children With Special Needs In Public Elementary Schools In Urban And Rural Areas - Ridho, Ali; Mahfudz Abd Qadir, Ach; Halim, Abdul (Journal of Islamic Elementary Education, 2025)
This study aims to analyze the implementation of inclusive education in realizing equitable access to education for children with special needs (CSN) in public elementary schools located in urban and rural areas. Employing a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis at two elementary schools with distinct geographic contexts. The findings indicate that schools in urban areas are generally more prepared to implement inclusive education in terms of internal policies, teacher competencies, and the availability of facilities. In contrast, rural schools face limitations in nearly all supporting aspects, including teacher understanding, physical infrastructure, and social environment support. The study concludes that a significant gap still exists between regions in the implementation of inclusive education, resulting in unequal access for CSN. Therefore, more context-sensitive policies and comprehensive interventions are required to ensure inclusive education can be effectively realized across all regions.